Moving around the city: discourses on walking and cycling in English urban areas - Jones, T; Pooley, C; Scheldeman, G; Horton, D; Tight, M; Mullen, C; Jopson, A; Whiteing, A (Pion, 2012)
There remains only limited understanding of perceptions of travel behaviour in relation to short journeys in urban areas and, in particular, the perceived role that walking and cycling for personal travel can realistically play in contemporary society. This paper reveals discourses surrounding the practice, performance, identity, conflicts and visions relating to walking and cycling in English cities. These were derived from a large-scale study that utilised a comprehensive mixed-method approach using both quantitative and qualitative methods. Q methodology was used as an additional tool to investigate subjectivities on walking and cycling in the city in a structured, interpretable format and it is this approach that is the focus of this paper. The paper concludes with a discussion on the implications of these discourses for policy makers interested in encouraging a shift from car use to walking and cycling for short journeys in urban areas.